2019
DOI: 10.1002/cite.201900040
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Diffusion Coefficients in Solutions of Lithium Bis(fluorosulfonyl)imide with Dimethyl Carbonate and Ethylene Carbonate

Abstract: Organic solutions of lithium bis(fluorosulfonyl)imide (LiFSI) are promising electrolytes for Li‐ion batteries. Information on the diffusion coefficients of the species in these solutions is needed for battery design. Therefore, the self‐diffusion coefficients in such solutions were studied experimentally with the pulsed‐field gradient nuclear magnetic resonance technique. The self‐diffusion coefficients of the ions Li+ and FSI− as well as those of the solvents were measured for LiFSI solutions in pure dimethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
(31 reference statements)
2
11
0
Order By: Relevance
“…As in the previous studies, Li + ion diffusion was observed to be the lowest (one order of magnitude lower than bis(fluorosulfonyl)imide(FSI)), despite having the smallest size, due to its strong coordination with the solvent molecules [119]. The diffusivity of ions in DMC was three times higher than those in EC [119]. Furthermore, the transport properties (self-diffusion coefficient and ionic conductivity) of LiPF6 and tris(pentafluoroethane)-trifluorophosphate (LiFAP) were measured in an EC:DMC mixture (50:50 w:w) [120].…”
Section: Methodssupporting
confidence: 71%
See 2 more Smart Citations
“…As in the previous studies, Li + ion diffusion was observed to be the lowest (one order of magnitude lower than bis(fluorosulfonyl)imide(FSI)), despite having the smallest size, due to its strong coordination with the solvent molecules [119]. The diffusivity of ions in DMC was three times higher than those in EC [119]. Furthermore, the transport properties (self-diffusion coefficient and ionic conductivity) of LiPF6 and tris(pentafluoroethane)-trifluorophosphate (LiFAP) were measured in an EC:DMC mixture (50:50 w:w) [120].…”
Section: Methodssupporting
confidence: 71%
“…The error in the experimentally measured Li + transference numbers (using the PFG-NMR method) was estimated to be 5 % and 20 % in binary and ternary solutions, respectively [117]. In addition, organic solutions of lithium bis(fluorosulfonyl)imide (LiFSI) in DMC, EC, or mixtures of them [55,118] were also investigated at 298 K using the PFG-NMR method [119]. As in the previous studies, Li + ion diffusion was observed to be the lowest (one order of magnitude lower than bis(fluorosulfonyl)imide(FSI)), despite having the smallest size, due to its strong coordination with the solvent molecules [119].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The B parameters, which corresponds to activation energy of the ion transport, of the ionic gels also increased with increasing of the [Li]/[O] molar ratio. It is known that increase of Li ion concentration in carbonate solutions decreased self‐diffusion coefficients of Li and counter anion 24,25 . The self‐diffusion coefficient corresponds to the activation energy of the ion transport, and decrease of the self‐diffusion coefficient increases the activation energy.…”
Section: Resultsmentioning
confidence: 99%
“…− 10 'W 𝑚 + /𝑠, which is comparable to the values reported for Na + in organic electrolytes conventionally used in rechargeable batteries 26,[95][96][97] . Experimental measurements [98][99][100] and numerical calculations [101][102][103][104][105] indicate that the diffusion coefficient of Li + is in almost the same range (sometimes even lower) in different battery electrolytes. This means that with WiS electrolytes, water can be used in batteries as a safe, available, and environmentally friendly solvent, while the diffusion coefficient of ions, which is expected to be greatly reduced due to the very high salt concentrations of WiS solutions 26 , is still within the working range of batteries.…”
Section: Wis Electrolytes In Rechargeable Batteriesmentioning
confidence: 99%